Effect of wastewater on the spring water quality of Sarida Catchment – West Bank. Issue 1 (1st January 2021) - Ahmad, Waseem; Ghanem, Marwan
Abstract: This research assessed the effect of untreated wastewater discharged to Sarida Wadi within the Sarida Catchment in the Central West Bank. Spring water from seven springs within the catchment were tested for physical, hydrochemical, and microbiological characteristics in wet and dry seasons. Hydrochemical results of wastewater samples showed that Total Suspended Solids (TSS) and Biological Oxygen Demand (BOD5 ) exceeded the standards in 93 percent of the samples, and an increase of COD value was recorded in the catchment downstream in the dry season. The springs' hydrochemical data showed that Ca 2+ plays a dominant role, and samples from the dry season exceeded the limits for HCO3 - . One spring showed high nitrate values, exceeding the 45 mg/L limit. The springs' microbial results provided overwhelming proof of wastewater contamination and an increasing trend over time of Fecal Coliforms (FC). The analyzed trace elements did not exceed World Health Organization (WHO) guidelines for drinking water with the exception of one spring with an abnormal value for Boron.